Inefficient lock-in and subsidy competition - Rainald Borck; Hyun-Ju Koh; Michael Pflüger (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper shows that subsidy competition may be efficiency enhancing. We model a subsidy game among two asymmetric regions in a new trade model, where capital can freely move among regions, but capital rewards are repatriated. We study subsidy competition, starting from an equilibrium where the industry core is inefficiently locked in to the smaller region. When regions weigh workers' and capitalists' welfare equally, the core region will set its subsidy low enough that the industry relocates to the larger region, restoring an efficient allocation. When workers' welfare is weighted more heavily, the core may pay subsidies that are high enough to prevent a relocation of industry.
Keywords: F12; F15; H25; H73; R12; 330; Agglomeration; asymmetric regions; subsidy competition; Subvention; Standortwettbewerb; Regionale Konzentration; Neue Außenhandelstheorie; Theorie